Crescimento e partição de assimilados de pimentão em função de arranjos espaciais e espaçamentos na fileira - Silva, Paulo Igor Barbosa e (2008)
Planting density is associated with management practices and competition for water, light, and nutrients, and consequently with crop growth. The study was carried out in 2006 in Baraúna-RN, Brazil, in order to characterize Atlantis green pepper growth at various spatial arrangements (1.5 m × 0.5 m; 1.6 m × 0.4 m; and 1.7 m × 0.3 m) and row spacings (0.2 m; 0.3 m; 0.4 m; and 0.5 m), arranged in a factorial combination. Nine growth assessment seasons (spaced 14 days apart, with the first performed 14 days after transplanting, DAT) were organized in split-plots. A completely randomized block design with three replicates was used. Increases were observed until 126 DAT in plant height (PH), leaf area (LA), leaf area index (LAI), leaf dry matter (LDM), stem dry matter (SDM), fruit dry matter (FrDM), and total dry matter (TDM) of theabove-ground part, and absolute growth rate (AGR); however, continuous reductions were observed in net assimilation rate (NAR), relative growth rate (RGR), and leaf area (LAR) and leaf weight ratio (LWR). Plant arrangement did not influence green pepper growth. Alterations in PH, LA, RGR, LWR, and LAR did not depend on row spacing; however row spacing influenced LDM, SDM, FrDM, and TDM, LAI, and AGR. Increased row spacing reduced PH, LAI, and LAR, and increased LA, LDM, SDM, FrDM, TDM, AGR, and NAR, but did not influence RGR and LWR. As spacing increases, the proportions of leaf dry mass and especially stem dry mass tend to decrease, while fruit dry mass tends to increase. When considering the period of initial fruit formation alone, the fruit dry mass proportions at row spacings of 0.2; 0.3; 0.4; and 0.5 m were 30.6%, 37.0%, 36.9%, and 36.5%, respectively